The global economic challenges in light of financial globalization and its impact on Corona epidemic spread - Hayder Basim Kareem; Mohammed Hussein Ali (Peerian Journals Publishing, 2023)
This research focused on studying the challenges facing global economies in the light of the spread of the Corona pandemic and the extent of the impact of this epidemic on financial globalization, and on answering a number of questions: Will the outbreak of the Corona virus lead to countries re-nationalizing their productive sectors, which means the end of globalization policies And the return of the state? And know the repercussions of this crisis. Will we go to another approach of globalization? And knowing whether this crisis will have a significant and continuing impact or will end its impact on the global economy, as happened during previous crises such as the global financial crisis that occurred in a year. The research concluded that after the retreat of the Corona epidemic, the feasibility of the structures of regional blocs, especially the European Union, should be reconsidered, and the form of political, economic, security and human relations between the various international regimes should be reconsidered, seeking to increase capital and foreign direct investment flows to developing countries, and to allow exporting countries For the capital by creating large investment opportunities more profitable in front of its accumulated surplus and providing guarantees for the owners of these funds and scope for diversification against many risks thanks to the mechanisms provided by financial instruments and arbitration between different markets
Keywords: mechanisms; front; developing countries; financial instruments